Trends in immediate breast reconstruction and early complication rates among older women: A big data analysis. Issue 7 (13th April 2017) - Kamali, Parisa; Curiel, Daniel; van Veldhuisen, Charlotte L.; Bucknor, Alexandra E.M.; Lee, Bernard T.; Rakhorst, Hinne A.; Lin, Samuel J.
Abstract : Background: Although approximately 57% of breast cancer (BC) diagnoses are in older patients (>60 years), only 4.1‐14% receives breast reconstruction (BR). This has been attributed to physician concerns about operative complications. This paper aims to: 1) analyze the 30‐day complication rates in the older patient population undergoing immediate breast reconstruction (IBR); and 2) analyze links between complication type and category of reconstruction. Methods: Using the ACS‐NSQIP database (2005‐2014), all women older than 60 years of age diagnosed with BC and DCIS were identified. IBR and complication rates were plotted for all ages. Patients were divided into those with and those without complications. Patient demographics and co‐morbidities were compared. Complications within each type of reconstruction were analyzed. Results: Of the 4450 BC and 1104 DCIS patients, 22.3% (BC) and 20.9% (DCIS) had complications. IBR decreased significantly with increased age ( P < 0.00 in both cohorts), while complication rates remained stable across all ages ( P = 0.32 in BC, P = 0.69 in DCIS patients). Patients were well matched in terms of demographics. Conclusions: The rates of breast reconstruction decrease with increasing age. Despite increasing age, associated complication rates in IBR patients remained stable.